Accelerating the Height Increase of Mersawa (Anisoptera marginata) Seedlings through Inundation Height with and without Water Treatments - Achmad, Basir; Faisal; Suhartati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Deforestation on peatlands in Indonesia has become an important issue. To restore the peatland condition, planting native tree species such as mersawa (Anisoptera marginata) is required. One of the problems with planting is the frequent occurrence of inundation at planting sites. The study aimed to analyze the inundation height, which accelerated the height increase of mersawa seedlings in acid or neutral water conditions. The method used was experimental research with a factorial completely randomized design. Factors studied were inundation height, consisting of without inundation, inundation at polybag height, inundation between the tips of the polybags and the apices of the plants, and inundation reaching the apices of the plants. The water composition consisted of peat swamp water, peat swamp water mixed with boiler ash from palm oil mill, and peat swamp water mixed with dolomite lime. The treatment of inundation between the tips of the polybags and the apices of the plants led to the highest height growth, while the lowest were the seedlings without inundation. The interaction between the inundation height and the water composition had a survival percentage of 100%, while the seedlings inundated up to the seedling apices with water treatments had a survival rate of 16%. Keywords: Anisoptera marginata, inundation, peat swamp water, seedling growth